2011
DOI: 10.1109/tit.2011.2165129
|View full text |Cite
|
Sign up to set email alerts
|

Information-Theoretic Analysis of MIMO Channel Sounding

Abstract: The large majority of commercially available multiple-input multiple-output (MIMO) radio channel measurement devices (sounders) is based on time-division multiplexed switching (TDMS) of a single transmit/receive radio frequency chain into the elements of a transmit/receive antenna array. While being cost-effective, such a solution can cause significant measurement errors due to phase noise and frequency offset in the local oscillators. In this paper, we systematically analyze the resulting errors and show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…But the practical implementation of MIMO systems experience random independent phase perturbations termed as phase noise due to transmit and receive oscillators [2], and thus suffers performance degradation [3]. In particular the effect of phase noise is more detrimental in OFDM systems [4].…”
Section: Introductionmentioning
confidence: 99%
“…But the practical implementation of MIMO systems experience random independent phase perturbations termed as phase noise due to transmit and receive oscillators [2], and thus suffers performance degradation [3]. In particular the effect of phase noise is more detrimental in OFDM systems [4].…”
Section: Introductionmentioning
confidence: 99%
“…The numerical evaluation of these bounds is often based on the algorithm for the computation of the information rates for finite-state channels proposed in [16] (see [17] for different approaches based, e.g., on particle filtering). Although the effect of phase noise in the measurement of MIMO channels has been extensively investigated in the literature (see, e.g., [18]), little is known about the impact of phase noise on the MIMO capacity. In [6], it was shown that different RF circuitries configurations (e.g., independent oscillators at each antenna as opposed to a single oscillator driving all antennas) yield different spatial multiplexing gains.…”
Section: Introductionmentioning
confidence: 99%
“…The phase noise manifests in a MIMO system as the random, time-varying phase differences between the oscillators connected to the antennas at the transmitter and the receiver. Practical designs of MIMO systems based on this assumption can result in significant performance losses and have to be addressed appropriately [2]. The detrimental effects of phase noise can be even more pronounced in scenarios where independent oscillators are connected to each transmit and receive antenna (or a subset of them).…”
mentioning
confidence: 99%
“…One of the few works investigating this problem can be found in [16], where the VB framework is employed. In general, MIMO receiver design has focused on developing algorithms for joint channel estimation and data detection (refer to [19], [20] and the references therein)-it is perceived that the phase noise can be handled by existing channel estimation-data detection algorithms since it can be regarded to be a part of the channel [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation